4-Phenylpyridin-2-one derivatives: a novel class of positive allosteric modulator of the M1 muscarinic acetylcholine receptor - Mistry, Shailesh N.; Jörg, Manuela; Lim, Herman; Vinh, Natalie B.; Sexton, Patrick M.; Capuano, Ben; Christopoulos, Arthur; Lane, J. Robert; Scammells, Peter J. (American Chemical Society, 2015)
Positive allosteric modulators (PAMs) of the M1 muscarinic acetylcholine receptor (M1 mAChR) are a promising strategy for the treatment of the cognitive deficits associated with diseases including Alzheimer’s and schizophrenia. Herein, we report the design, synthesis, and characterization of a novel family of M1 mAChR PAMs. The most active compounds of the 4-phenylpyridin-2-one series exhibited comparable binding affinity to the reference compound, 1-(4-methoxybenzyl)-4-oxo-1,4-dihydroquinoline-3-carboxylic acid (BQCA) (1), but markedly improved positive cooperativity with acetylcholine, and retained exquisite selectivity for the M1 mAChR. Furthermore, our pharmacological characterization revealed ligands with a diverse range of activities, including modulators that displayed both high intrinsic efficacy and PAM activity, those that showed no detectable agonism but robust PAM activity and ligands that displayed robust allosteric agonism but little modulatory activity. Thus, the 4-phenylpyridin-2-one scaffold offers an attractive starting point for further lead optimization.